2010
DOI: 10.1186/1475-2891-9-49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambrotose AO® on resting and exercise-induced antioxidant capacity and oxidative stress in healthy adults

Abstract: BackgroundThe purpose of this investigation was to determine the effects of a dietary supplement (Ambrotose AO®) on resting and exercise-induced blood antioxidant capacity and oxidative stress in exercise-trained and untrained men and women.Methods25 individuals (7 trained and 5 untrained men; 7 trained and 6 untrained women) received Ambrotose AO® (4 capsules per day = 2 grams per day) or a placebo for 3 weeks in a random order, double blind cross-over design (with a 3 week washout period). Blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…These findings are supported by previous literature, in particular with regards to higher oxidative stress in men compared to women [47] and in obese compared to overweight and/or normal weight subjects [48,49]. With regards to the antioxidant capacity in exercise-trained compared to untrained subjects, mixed results are available; some supporting our finding of lower antioxidant capacity in trained individuals [50] and some refuting this [51,52]. Those findings in support of our data may be linked to the acute increase in ROS experienced by exercise-trained individuals, which may partially deplete endogenous antioxidants over time [50].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are supported by previous literature, in particular with regards to higher oxidative stress in men compared to women [47] and in obese compared to overweight and/or normal weight subjects [48,49]. With regards to the antioxidant capacity in exercise-trained compared to untrained subjects, mixed results are available; some supporting our finding of lower antioxidant capacity in trained individuals [50] and some refuting this [51,52]. Those findings in support of our data may be linked to the acute increase in ROS experienced by exercise-trained individuals, which may partially deplete endogenous antioxidants over time [50].…”
Section: Discussionsupporting
confidence: 90%
“…Ambrotose AO at a daily dosage of 4 capsules per day increases resting blood antioxidant capacity and may enhance post exercise antioxidant capacity. However, no statistically detected difference is observed in resting or exercise-induced oxidative stress biomarkers, in quality of life, or in tread mill test time to exhaustion [32] . Probiotic lactic acid producing bacteria have been shown to prevent and alleviate gastrointestinal disturbances and to normalize the cytokine profile which might be an advantage for patients suffering from chronic fatigue syndrome (CFS).…”
Section: E F F E C T O F a L O E V E R A J U I C E T O Chronic Fatigumentioning
confidence: 78%
“…The benefit of antioxidant supplementation on health outcomes have become of increasing interest due to controversial findings of both beneficial and non-beneficial, even detrimental effects in humans of high intakes of antioxidant supplementation ( Biesalski, Grune, Tinz, Zollner, & Blumberg, 2010 ; von Arnim et al, 2012) . The antioxidant preparation used have been shown in a 21-day randomized, double-blind, placebo-controlled crossover trial of 25 healthy adults to significantly increase two measures of antioxidant capacity in the blood: oxygen radical absorbance capacity (ORAC) and Trolox Equivalent Antioxidant Capacity (TEAC) ( Bloomer, Canale, Blankenship, & Fisher-Wellman, 2010 ). Two earlier open-label studies using the same preparation on healthy adults showed significant increases in serum ORAC, between 36.6% to 37.4%, compared with baseline ( Boyd et al, 2003 ; Myers et al, 2010) .…”
Section: Discussionmentioning
confidence: 99%